Peranan Orientasi Pasar dalam Hubungan Kinerja Perusahaan pada Industri Manufaktur di Solo Raya - Haryanto, Aris Tri; Dewi, Septiana Novita; Nugroho, Anggoro Panji (University of Merdeka Malang, 2020)
This study aims to provide additional benefits to the literature on the role of market orientation on the performance relationship of manufacturing industrial companies in Solo Raya. This type of research is a causality study with a sample size of 100 respondents, which is obtained from 5 times the number of parameters (20). The research uses path analysis which has a direct or indirect effect. The results of this study indicate: 1)Â responsive market orientation has a significant positive effect on marketing performance, 2) proactive market orientation has a significant positive effect on marketing performance, 3) responsive market orientation has a significant positive effect on financial performance, 4) Complaint handling has no significant negative effect on financial performance, 5) Marketing performance has a significant positive effect on financial performance. The result of the direct effect of responsive market orientation on financial performance is smaller than the indirect effect. The direct effect of proactive market orientation on financial performance is smaller than the indirect effect. It shows Â that all are effective through direct channels without going through the mediating variable.https://doi.org/10.26905/jmdk.v8i2.4109